2013
DOI: 10.1371/journal.pone.0056852
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in p38β MAPK Fails to Inhibit Cytokine Production or Protect Neurons against Inflammatory Insult in In Vitro and In Vivo Mouse Models

Abstract: The p38 MAPK pathway plays a key role in regulating the production of proinflammatory cytokines, such as TNFα and IL-1β, in peripheral inflammatory disorders. There are four major isoforms of p38 MAPK (p38α, β, δ, γ), with p38α and p38β the targets of most p38 MAPK inhibitor drugs. Our previous studies demonstrated that the p38α MAPK isoform is an important contributor to stressor-induced proinflammatory cytokine up-regulation and neurotoxicity in the brain. However, the potential role of the p38β MAPK isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
5
17
0
Order By: Relevance
“…Considering the severity of phenotypes in isoform specific knockout mice, p38α MAPK seems to be the major isofom of the family at least during development and inflammatory responses, although p38β MAPK, p38γ MAPK, and p38δ MAPK have also pivotal roles under other conditions. (Aouadi, Binetruy, Caron, Le Marchand-Brustel, & Bost, 2006; Xing, Bachstetter, & Van Eldik, 2013). …”
Section: Cellular Function Of P38 Map Kinasesmentioning
confidence: 99%
“…Considering the severity of phenotypes in isoform specific knockout mice, p38α MAPK seems to be the major isofom of the family at least during development and inflammatory responses, although p38β MAPK, p38γ MAPK, and p38δ MAPK have also pivotal roles under other conditions. (Aouadi, Binetruy, Caron, Le Marchand-Brustel, & Bost, 2006; Xing, Bachstetter, & Van Eldik, 2013). …”
Section: Cellular Function Of P38 Map Kinasesmentioning
confidence: 99%
“…In this system, the two kinds of cells share the same medium and interact through diffusible molecules only. As reported by others, we adopted the Neurobasal medium to meet higher nutrition requirements for neurons (Xing et al, 2013). Before OGD/R treatment, microglia and neurons were co-cultured 24 h for utmost microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…73 Using cells within the CNS, several studies have demonstrated that the p38 MAPKa isoform is a relatively more important contributor to stressor-induced proinflammatory cytokine production and neurotoxicity compared with the p38b isoform. [74][75][76] Several studies have reported that SB203580, a typical inhibitor of p38 MAPKa and p38 MAPKb, rescues RGCs from NMDA and optic nerve injury, suggesting the involvement of p38 MAPKa and p38 MAPKb in RGC survival. 77,78 However, the roles of the other p38 isoforms in neuronal cells have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%